Editorial - Muzafer Mujic (Biomolecules & Biomedicine, 2004)
We inform our readers and collaborators that the interest for publication in Bosnian Journal of Basic Medical Sciences is growing continuously. Numerous letters and messages (e-mail) of support, in particular from our scientists working abroad, are sufficient confirmation. This exchange resulted in the idea (E. Kanlic, MD PhD, Associate Professor, Dept. of Orthopedic, Texas) that our scientists working in the USA edit one issue (preliminary deadline in April 2005) that would be dedicated to the latest understandings and achievements in a specific area that would be of interest for our experts. We are looking forward to successful cooperation with other colleagues engaged in fundamental science. It is with great pleasure that we inform you that, after anticipating a reply from the Department of Health and Human Services for some time, on the 6th July 2004 we received an information from Mr. Sheldon Kotzin, Executive Editor MEDLINE/Index Medicus stating that Bosnian Journal of Basic Medical Sciences has received a positive score (very good) upon reviewing and has been accepted for indexation in MEDLINE/Index Medicus We are proud that our issues are mainly filled with papers by young researchers which agrees with our primary intention that the Journal grows into a vehicle for the exchange of knowledge among young researchers in the world. With this issue we complete the cycle for this year. We are convinced that, despite significant difficulties, we will find adequate support and ensure regular publication of research results from the entire Bosnia and Herzegovina. With sincere greetings and gratitude, Sarajevo, October 2004 Editorial and Advisory Board M.Mujic This Journal is Indexed in: CAB Abstract / Global Health databases and Index Medicus/MEDLINE.